American Catholics in the Protestant Imagination: Rethinking the Academic Study of Religion - Carroll, Michael P. (Johns Hopkins University Press, 2007)
Michael P. Carroll argues that the academic study of religion in the United States continues to be shaped by a "Protestant imagination" that has warped our perception of the American religious experience and its written history and analysis.In this provocative study, Carroll explores a number of historiographical puzzles that emerge from the American Catholic story as it has been understood through the Protestant tradition. Reexamining the experience of Catholicism among Irish immigrants, Italian Americans, Acadians and Cajuns, and Hispanics, Carroll debunks the myths that have informed much of this history.Shedding new light on lived religion in America, Carroll moves an entire academic field in new, exciting directions and challenges his fellow scholars to open their minds and eyes to develop fresh interpretations of American religious history.